Answer:
Step-by-step explanation:
7). (x + 3)(x + 7)
= x(x + 7) + 3(x + 7)
= x² + 7x + 3x + 21
= x² + 10x + 21
8). (4x + 2)(x - 2)
= 4x(x - 2) + 2(x - 2)
= 4x² - 8x + 2x - 4
= 4x² - 6x - 4
9). (3x + 2)(2x + 5)
= 3x(2x + 5) + 2(2x + 5)
= 6x² + 15x + 4x + 10
= 6x² + 19x + 10
10). (x² - 6)(x - 4)
= x²(x - 4) - 6(x - 4)
= x³ - 4x² - 6x + 24
11). (x² + 9)(x - 3)
= x²(x - 3) + 9(x - 3)
= x³ - 3x² + 9x - 27
12). (4x²- 4)(2x + 1)
= 4x²(2x + 1) - 4(2x + 1)
= 8x³ + 4x² - 8x - 4
Answer:
(j-3)/3 =k
Step-by-step explanation:
j+2 = 3k+5
Solve for k
Subtract 5 from each side
j+2-5 = 3k+5-5
j-3 = 3k
Divide each side by 3
(j-3)/3 = 3k/3
(j-3)/3 =k
The Answer Is B Because Count The Number Of Hours By The Amount Of Money He Is Being Paid
Good evening ,
______
Answer:
1) (f+g)(1) = e
2) (fg)(1) = 0
3) (3f)(1) = 3e
___________________
Step-by-step explanation:
1) (f+g)(1) = f(1) + g(1) = e¹ + log1 = e + 0 = e.
2) (fg)(1) = f(1) × g(1) = e¹ × log(1) = e¹ × 0 = e × 0 = 0.
3) (3f)(1) = 3×f(1) = 3×e¹ = 3e.
:)